PENGARUH PENCANTUMAN LABEL HALAL PADA KEMASAN MIE INSTAN TERHADAP MINAT PEMBELIAN MASYARAKAT MUSLIM (Studi Kasus Pada Mahasiswa Universitas Al-Washliyah, Medan) - Yuli Mutiah Rambe; Syaad Afifuddin (Departemen Ekonomi Pembangunan USU, 2012)
This research intends to find out the influence of including the halal lable on the packaging of instant noodles (Indomie) to the buying interest in students of the University of Al-Washliyah, Medan as well as to find out the influence of including the halal lable on packaged food products in the mind of students from the University of Al-Washliyah, Medan. The technique of data collection is with collecting the data directly in the research location with questionnaires. The primary data obtained from the questionnaires (statement) lists were processed by using SPSS 17.0 and the hypothesis testing was done by using the product moment formula of Karl Pearson to see the halal lable to the buying interest. The data analysis performed showed the correlation coefficient of product moment with the symbol rxy by 0.557, where the level of significance was 0.000, the relation from or influence occured, was positive. The determinant coefficient of the formation of variable Y to X was 0.311 which means that the variable X gived an influence to the height or lowness of variable Y by 31.1%.